Introduction to Inpatient Procedures: A Resident-to-Resident Guide - James Abraham; Basel Al-Aloul; Syed Sohail Ali; Patrick Foy; JoEllen Kohlman; Haresh Kumar; Katherine Marienfeld (Association of American Medical Colleges, 2008)
Abstract This handbook contains common inpatient procedures developed by internal medicine residents specifically for resident and medical student use. It includes discussion of aseptic technique, procedure documentation, central venous catheter review, and detailed clinical discussions regarding six common inpatient procedures in a concise, high-yield format suitable for a busy inpatient service. This handbook was used in conjunction with a procedure workshop geared towards incoming internal medicine interns. It could also be extended to include medical students who are currently in their internal medicine clerkship. Procedures reviewed in this edition include internal jugular central venous catheter placement, femoral central venous catheter placement, radial arterial line placement, lumbar puncture, thoracentesis, and paracentesis. This handbook provides a systematic review of inpatient procedures and the issues that arise before and after performing them. Each procedure is reviewed in detail though in a high-yield format conducive to on-the-fly review while working on a busy inpatient medicine service.